Glória e legado do primeiro romântico: Gonçalves de Magalhães - Lima, Leandro Siqueira (2009)
This study concerns itself with the works of Gonçalves de Magalhães the usherer of romanticism in Brasil , the age in which he emerged and the criticism for and against the almost forgotten author. In the intention of investigating these, a common denominator was found in 3 principal works of the carioca author: the poem Carta ao meu amigo Dr. Candido Borges Monteiro , the article Ensaio sobre a História da Literatura Brasileira and the inaugural volume of poems in the Romantic Movement, Suspiros poéticos e saudades. This denominator the author in search of a justification for his creative activity is in exaggerations of reference to himself, and are exposed with total sincerity in works with little attraction, influencing generations of criticism to observe the figure of the author at the loss of his works.